PELATIHAN MEMBUAT SUSHI SEBAGAI SALAH SATU UPAYA MENCETAK WIRAUSAHAWAN - Noviana, Fajria; S.I., Trahutami; ANR, Elizabeth Ika Hesti; Rosliana, Lina (Departemen Linguistik, Fakultas Ilmu Budaya Universitas Diponegoro, 2017)
ABSTRACT Enterpreneurship workshop that matched with what have been learned in college is an effort to grow creative and enterpreneurhip spirit in students. Therefore, sushi making workshop for the students of Japanese Department in Diponegoro University Faculty of Humanities, is an example of that effort. This workshop can be some way to open new job vacancies, as well lessens the number of educated unemployment.Keywords : entrepreneurship, food, Japan, sushi